Comparison Study of Sorting Techniques in Static Data Structure - Frak, Anwar Naser; Saringat, Mohd Zainuri; Prasetyo, Yuli Adam; Mustapha, Aida; Aman, Hannani; Ibrahim, Noraini (International Journal of Integrated Engineering, 2018)
To manage and organize large data is imperative in order to formulate the data analysis and data processing efficiency. Therefore, this paper investigates the set of sorting techniques to observe which technique to provide better efficiency. Five types of sorting techniques of static data structure, Bubble, Insertion, Selection with O(n2) complexity and Merge, Quick with O(n log n) complexity have been used and tested on four groups between (100–30000) of dataset. To validate the performance of sorting techniques, three performance metrics which are time complexity, execution time and size of dataset were used. All experimental setups were accomplished using simple linear regression. The experimental results illustrate that Quick sort is more efficiency than other sorting and Selection sort is more efficient than Bubble and Insertion in large data size using array. In addition, Bubble, Insertion and Selection have good performance for small data size using array thus, sorting technique with behaviour O(n log n) is more efficient than sorting technique with behaviour O(n2) using array.